Pengaruh Social Experience, Trendiness dan E-WOM terhadap Purchase Intention Melalui Brand Awarness Sebagai Mediasi pada Social Media Marketing Produk Kecantikan di Socialla - Marisa Hargiana Ningrum; Ihwan Susila (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
One of the largest contributors to waste in Indonesia comes from skincare product waste, which has led both the government and companies to promote the shift towards green products. Society also plays a role in this through electronic word of mouth (e-WOM), and several other factors influence consumer purchase intention towards green products, such as social experience and trendiness. This study aims to analyze the impact of perceived social media marketing activities on purchase intention through factors like social experience, trendiness, and e-WOM in beauty product marketing on Sociolla. The research surveys consumers who have experience and purchase intention for green product skincare. Data are analyzed through convenience sampling, and the research hypotheses are examined using PLS-SEM. The practical implications of this study will assist e-commerce managers in enhancing consumer purchase intention on e-commerce platforms through social media marketing activities (SMMA). This research fills a gap in previous studies by addressing the disaggregation of social media in the context of green products, highlighting the limitations of social media in shaping consumer attitudes, and addressing the under-explored TPAM and U&G frameworks in prior research. This study aims to expand variables related to social media that can influence consumer attitudes and provide a more detailed understanding of green product marketing on social media.